Clinical Aspects of Food Allergy in Infants in Pleven Region, Bulgaria - Vanya Nedkova-Milanova; Tsvetelina Miteva; Darina Hristova; Lyubomira Gadjelova; Magdalena Balashkova (Journal of Biomedical & Clinical Research)
Food allergy is an immunoglobulin E-meditated reaction, to which the organism’s immune system reacts to a food allergen, recognizing it as harmful. The study aimed to establish at what age cow’s milk protein allergy is manifested and determine the values of immunoglobulin E (IgE) and hemoglobin(Hb) in children with CMPA in Pleven region, Bulgaria. The study included 94 infants presenting with clinical manifestations of food allergy (age range 0 to 12 months) from Pleven and Pleven region, consulted in 2017 by a pediatrician at the University Hospital Consulting Center in Pleven. Venous blood was collected to determine the IgE and Hb values. Chronic iron-deficiency anemia could be the only clinical manifestation in children with CMPA. Out of all the children with CMPA, 17% had a pronounced anemic syndrome. The rest had normal Hb values. Anemic syndrome could have severe consequences for a growing child. Elevated IgE values were found in 73% of the children tested. CMPA is frequently seen in infants. Early diagnosis of clinical manifestations and diet could prevent severe complications of allergy such as chronic diarrhea, chronic urticaria, and asthma.